SNAP-25 isoforms differentially regulate synaptic transmission and long-term synaptic plasticity at central synapses - Irfan, Muhammad (Sci Rep, 2019)
SNAP-25 exists as two developmentally regulated alternatively spliced isoforms, SNAP-25a and SNAP-25b. We explored the function of SNAP-25a and SNAP-25b at Schaffer collateral-CA1 synapses in hippocampus using 4-week-old wild-type (WT) and SNAP-25b-deficient (MT) mice. Characterizing the protein expression of individual SNAP-25 isoforms revealed that WT females had higher levels of SNAP-25a than WT males, suggesting a sex-dependent delay of the alternative splicing switch from SNAP-25a to SNAP-25b. MT mice expressed normal levels of total SNAP-25, Syntaxin 1A and SNAP-47 in the hippocampus, but females expressed lower levels of VAMP2. Electrophysiological recordings in in vitro hippocampal slices revealed significantly reduced magnitude of LTP in MT mice. We also found reduction in paired-pulse facilitation after induction of LTP in WT males, but not in WT females, possibly related to the difference in SNAP-25a/SNAP-25b ratios, suggesting that the splicing switch may play a sex-specific role in LTP-associated increases in presynaptic release probability. Basal synaptic transmission measured in input-output relations revealed that the ability to discriminate between the intensity of presynaptic stimuli was affected in SNAP-25b-deficient mice. Learning in a behavioural paradigm of active-avoidance was impaired in MT mice, strengthening the conclusion that SNAP-25b is important for cognitive performance by altering activity-dependent synaptic plasticity.